Synthesizing diverse evidence in policy research: From evidence pyramid to deliberative integration (Nepal Public Policy Review, 2025)
This editorial examines a central methodological challenge in contemporary policy research: how to synthesize diverse and extant evidence into credible policy knowledge. Policy inquiry increasingly draws on academic literature, policy and legal documents, gray literature, administrative records, media sources, and primary stakeholder data, creating conditions of evidence abundance rather than evidence scarcity. Building on recent reconsiderations of evidence hierarchies, the editorial adapts the evidence pyramid for policy research by positioning deliberative integration, rather than a single superior study design, at its apex as the highest order of synthesis and judgment. The pyramid’s layers are wavy, acknowledging that evidentiary strength depends not only on study design but also on the robustness and relevance of the findings. The model further argues that this hierarchy should be understood within an evidence ecosystem perspective, in which diverse forms of evidence interact as complementary elements rather than competing sources. Within this framing, deliberative integration is proposed as a structured process of triangulation, contextual interpretation, and transparent reconciliation of heterogeneous evidence, including adaptive use of expert judgment where uncertainty persists. The editorial argues that linking the evidence hierarchy, the evidence ecosystem, and the deliberative integration offers a more suitable framework for synthesizing complex evidence in policy research and for strengthening evidence-informed policymaking.